PROCESS FOR PREPARATION OF PURE POLYMORPHIC FORM 1 OF CLOPIDOGREL HYDROGENSULFATE (2008)
13 1414Process for the preparation of substantially pure polymorphic Form 1 of clopidogrel hydrogensulfate, wherein the reaction of optically active clopidogrel base with sulfuric acid is carried out in the mixture of at least two solvents, chosen from group I, comprising aliphatic ethers, and from group II, comprising ketones, esters of C-Ccarboxylic acids and aliphatic alcohols C-C, primary, secondary and tertiary aliphatic alcohols C-C, then the resulting suspension is stirred until at least 70% of amorphous clopidogrel hydrogensulfate formed is transformed into polymorphic Form 1 of clopidogrel hydrogensulfate, and finally, the crystalline solid is isolated from the reaction mixture and subject to additional work-up procedure, aiming at the formation and stabilization of polymorphic Form 1.